RANCANG BANGUN APLIKASI PERCETAKAN TIGA BERSAUDARA BERBASIS WEB DENGAN METODE WATERFALL - Ardian Shalihin Ardian; Nawassyarif; Yunanri. W (Jurnal Informatika Teknologi dan Sains, 2021)
In line with the rapid development of technology and the increasing number of supporting facilities, people have started to use various computerized services because it is easier and there are many choices that can simplify all the needs that must be met and resolved. This can be seen from the use of information technology in various fields such as the printing business. The three brothers' printing company promotes products that are made manually, by distributing brochures around the printing area, word of mouth, as well as placing banners in front of the printing house. This study aims to build applications web. This application was built using the programming PHPlanguage with the CodeIgniter framework, MySQL database. The data collection technique instruments in this study were interviews, literature study and observation. The software development method uses the method, waterfall namely software requirements analysis, design, programming and testing. As well as the software testing method using testing black-box. The final result of this research is as a medium for customers to know all the products contained in the printing of the three brothers and can immediately ask or consult about the desired product. Thebased Three Brothers Printing Application Web- has been completed using the programming PHP language with the CodeIgniter framework, a MySql database that uses the method waterfall up to the testing stage using a blackbox. Testing using blackbox to users involving 20 respondents can be concluded that this application is feasible to use and the application runs well.